There are three major Neisseria gonorrhoeae β-lactamase plasmid variants which are associated with specific lineages and carry distinct TEM alleles - Elsener, TA; Jolley, KA; Sanders, E; Maiden, MCJ; Cehovin, A; Tang, CM (Microbiology Society, 2023)
Neisseria gonorrhoeae is a significant threat to global health with an estimated incidence of over 80 million cases each year and high levels of antimicrobial resistance. The gonococcal β-lactamase plasmid, pbla, carries the TEM β-lactamase, which requires only one or two amino acid changes to become an extended-spectrum β-lactamase (ESBL); this would render last resort treatments for gonorrhoea ineffective. Although pbla is not mobile, it can be transferred by the conjugative plasmid, pConj, found in N. gonorrhoeae. Seven variants of pbla have been described previously, but little is known about their frequency or distribution in the gonococcal population. We characterised sequences of pbla variants and devised a typing scheme, Ng_pblaST that allows their identification from whole genome short-read sequences. We implemented Ng_pblaST to assess the distribution of pbla variants in 15 532 gonococcal isolates. This demonstrated that only three pbla variants commonly circulate in gonococci, which together account for >99 % of sequences. The pbla variants carry different TEM alleles and are prevalent in distinct gonococcal lineages. Analysis of 2758 pbla-containing isolates revealed the co-occurrence of pbla with certain pConj types, indicating co-operativity between pbla and pConj variants in the spread of plasmid-mediated AMR in N. gonorrhoeae. Understanding the variation and distribution of pbla is essential for monitoring and predicting the spread of plasmid-mediated β-lactam resistance in N. gonorrhoeae.